Endoscopic assessment and Helicobacter pylori status evaluation in operated cases of peptic ulcer perforation - Rao, Prashant; Mayekar, Sarika; Pawar, Vishwajit; Joshi, Mohan Achyut (International Surgery Journal, 2020)
Background: Helicobacter pylori’s role in delaying ulcer healing after surgical repair for peptic ulcer perforation causing ulcer persistence hasn’t been definitively established as it has been for uncomplicated ulcers. Methods: Authors performed an endoscopy and H. pylori status evaluation in 30 patients at an average of 6.2 weeks after simple omental patch closure for perforated peptic ulcer. Results: A positive H. pylori status was found in 12 patients (40%) of which 9 had active ulcers. None in the negative group had an active ulcer. H. pylori infection was the only factor found to be responsible for ulcer persistence after surgery. Conclusions: A reasonable approach would thus be to perform an endoscopy 6 weeks after surgery to assess ulcer healing and H. pylori status. H. pylori eradication therapy should then be selectively initialled for patients with an active ulcer or positive H. pylori status.